Motor and cognitive decline of healthy elderly and elderly with parkinson’s disease - a cross-sectional study - Gomes, Wildja de Lima; Silva, Neildja Maria da; Silva, Laize Gabriele Castro; Cacho, Ênio Walker Azevedo; Cacho, Roberta de Oliveira; Cruz, Maria do Socorro Luna; Lima, Núbia Maria Freire Vieira (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Parkinson’s disease (PD) was initially described as a movement disorder, however there is now recognition that its clinical features also include non-motor symptoms such as cognitive impairment and dementia, which are frequent even in the early stages of the disease and, especially in the advanced stages. Cognitive deficits in PD include impairments in executive functions, attention, memory, and visuospatial skills. Cognitive impairment may manifest as mild cognitive impairment (MCI) or dementia, in which MCI refers to the stage between normal cognitive functioning and dementia. Factors associated with cognitive dysfunction in PD include advanced age, low schooling, worse motor scores, stiffness, postural instability and increased daytime sleepiness. Objective: To track cognitive decline and to correlate measurement instruments in subjects with PD by comparing them to healthy subjects. Methods: Study conducted at the Faculty of Health Sciences of Trairi / UFRN. The sample consisted of 20 old people (10 healthy elderlies and 10 elderlies with PD). It was applied the socio-demographic record, Unified Parkinson’s Disease Rating Scale (UPDRS II and III), Hoehn & Yahr Scale, Mini Mental State Examination, Leganés Cognitive Test (LCT) and Montreal Cognitive Assessment (MoCA). Results: It was observed cognitive decline in both groups by MoCA (90% of the PD group and 80% of the healthy group), with no statistically significant difference (p=0.10). It was also verified association between UPDRS II and LCT (r= -0.69, p=0.03) and between UPDRS III and LCT (r=-0.66, p=0.04). Conclusion: We found a cognitive deficit in the elderly group with PD, with no significant difference when compared to the healthy elderly. There was an association between motor and cognitive function in subjects with PD. MoCA was more sensitive in the screening of cognitive deficit in subjects with PD.